Green Concrete for a Better Sustainable Environment - Tang, Patrick (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book, Green Concrete for a Better Sustainable Environment, aims to cover recent advances in the development of green concrete solutions and discuss the best ways to leverage opportunities in this domain. Concrete can be described as green concrete if it has one of the following features; it uses waste material as at least one of its components, its production process does not lead to environmental destruction, or it has high performance and life cycle sustainability. At present, natural resources are running out. Cement and concrete made from industrial and construction waste can be regarded as valuable resources for civil infrastructure construction. Green concrete will not only contribute to a circular economy, but can also help to reduce the amount of embodied energy and CO2 emissions associated with cement manufacturing and aggregate quarrying. Using green concrete can also mitigate the environmental threats associated with industrial waste materials. This book covers the theoretical, experimental, applied and modelling research studies on the materials, products and structures related to sustainable cement-based composites.